Green entrepreneurial orientation and green human capital: unlocking the potential of green supply chain integration through corporate environmental strategy - Wencheng Zhang; Fengjuan Zhang; Zhuo Cheng (Humanities & Social Sciences Communications)
Abstract Our research explores the effects of green entrepreneurial orientation, green human capital, and corporate environmental strategy on green supply chain integration in the context of Chinese manufacturing firms. Grounded in the resource-based view, this study asserts that these constructs are crucial as internal resources contribute to sustainable competitive advantage. This study employs a systematic random sampling approach for data collection, targeting senior managers across key industrial sectors in China, including renewable energy, waste management, and green construction. By surveying 316 Chinese manufacturing enterprises and utilizing the partial least squares structural equation modeling technique, this paper reveals significant direct relationships among green entrepreneurial orientation, green human capital, corporate environmental strategy, and green supply chain integration. Additionally, we identify corporate environmental strategy as a critical mediating factor among the associations. The research contributes to the resource-based view by illustrating the potential of environmentally focused resources in promoting green innovation and integration. Our findings also reveal the significant importance of corporate environmental strategies in establishing a connection between green entrepreneurial efforts, human capital, and supply chain practices. Moreover, the study offers crucial strategic insights for manufacturing organizations seeking to align their entrepreneurial initiatives effectively, investments in human capital, and environmental plans to improve sustainability in their supply chain operations.